PENGARUH BRAND IMAGE, BRAND LOYALTY DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SANFORD DI KOTA BATAM - Nani Nani; Tiurniari Purba (LPPM Universitas Putera Batam, 2026)
The development of the globalization era is characterized by the dynamics of increasing business competition, companies are required to be able to maintain their business continuity through the implementation of integrated marketing strategies and oriented to consumer needs. This study aims to analyze the influence of brand image, brand loyalty, and product quality on Sanford purchasing decisions in Batam City. This study uses a quantitative approach using questionnaires distributed to 96 respondents in Batam City. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results of the study indicate that brand image has a positive and significant effect on Sanford product purchasing decisions in Batam City. Brand loyalty has a positive and significant effect on Sanford product purchasing decisions in Batam City. Product quality has a positive and significant effect on Sanford product purchasing decisions in Batam City. Brand image, brand loyalty, and product quality simultaneously have a significant effect on Sanford product purchasing decisions in Batam City.